Pengaruh Abu Sekam terhadap Populasi dan Serangan Lalat Kacang (Ophiomyia phaseoli) pada Tanaman Kedelai - Norman Wijaya; Ato Sulistyo; Subagiya Subagiya; Susilo Hambeg Poromarto (Agrotechnology Research Journal, 2023)
The bean fly (Ophiomyia phaseoli) is a major pest of soybean in Indonesia which causes the plants to die early in growth. Most farmers use insecticide synthetics to control this pest. Therefore the alternative control of bean flies is needed to reduce reliance on farmer's usage of chemical pesticides. One of the alternative control is with application of husk ash that has a high silica content. This study examined husk ash to know the effect of husk ash to population and proportion of bean flies attacks. This research conducted in Pengkok Village, Kedawung, Sragen from June - September 2019. The method used was field experiment with a Randomized Completely Block Design (RCBD) with one factor, namely the dose of husk ash five levels (0 tons ha-1, 1.25 tons ha-1, 2.5 tons ha-1, 3.75 tons ha-1, and 5 tons ha-1) and five replications. The results showed that the application of husk ash not affected significantly on the adults of the bean fly population, but affected significantly the percentage of attacks only in the cotyledons. The application of rice husk ash can reduce the percentage of attack on the cotyledons by 2.11-3.04% than without husk ash application. The number of plant deaths apparently followed the populations of bean flies. Furthermore, the height of soybean with application looked taller than without application.